ALTERNATIVE CONCEPTIONS OF STUDENTS X EPISTEMOLOGY OF LAKATOS (Fiep Bulletin - online, 2020)
This paper presents a teaching proposal that emerges from students' alternative conceptions on a theme for a teaching sequence based on Lakatos epistemology, that enables the discussion of science through historical aspects, aiming to contribute to the construction of the knowledge in science teaching. The proposal was conceived from the analysis of the results of a research done on the initial conceptions of students about the pesticide theme carried out with a total of thirty students of the 3rd grade of the public school system in the southern region of Paraná, Brazil. The results revealed the possibility of the teacher acting as a mediator of the teaching process in which the students' conceptions were organized in a model in which the scientific theories are generated, produced by the protagonism of the students in choosing a concept that best characterizes the studied theme.